HUBUNGAN POLA ASUH ORANG TUA DENGAN STATUS PERTUMBUHAN PENDIDIKAN ANAK USIA DINI (PAUD) DI PAUD HALELUYA DAN CEMARA LILIBA KOTA KUPANG - Ndun, Melda; Setia, Agustina; Mali, Alberth Matu Salak Bau (Poltekkes Kemenkes Kupang, 2025)
Parenting is a pattern of interaction between parents and children, especially attitudes or behavior when interacting with children, such as how to enforce rules, instill values ​​and norms, show affection and behave well so that they become role models for their children. Changes in physical size over time in terms of dimensions, proportions, and body composition are referred to as growth and development. The growth process is quantitative in nature, showing changes that can be observed physically. By measuring body weight (BB), height/body length (TB/PB), and so on, growth can be observed.This research aims to determine the relationship between parenting patterns and the growth status of PAUD children in PAUD Halleluya and Cemara Liliba, Kupang City. This type of researcher uses quantitative analysis with a cross-sectional method approach. The data analysis used was the chi square test. From the research results, it was found that the frequency of parenting attitudes with the most negative parenting attitudes, namely the attitudes of pampering, allowing and controlling, amounted to 53 respondents with a percentage of (63.9%). Namely, the attitude of pampering parenting was 21 respondents (25.3%), the attitude of letting parenting was 17 respondents (20.5%) and the attitude of controlling parenting was 15 respondents (18.1%). The frequency of children's growth status based on BMI in the normal category was 61 respondents (73.5%), in the thin category 15 respondents (18.1%), in the fat category 4 respondents (4.8%) and in the obesity category 3 respondents (3.6%). The results of the analysis stated that there was a relationship between parenting patterns and children's growth in body mass index (BMI), indicated by a p value of 0.000.